Characteristics of Silica Sand Shipyard Sandblasting Waste as Construction Materials - Kiki Dwi Wulandari; Widya Emilia Primaningtyas; Benedicta Dian Alfanda; Wahyuniarsih Sutrisno (POLITEKNIK NEGERI BENGKALIS, 2022)
Silica sand as by-product waste is a major contributor to the volume of waste generated by sandblasting activities in the shipping industry. Based on a survey conducted during 2020-2022, silica sand in the shipping industry in East Java is around 450 tons/year. Silica sand has potential utilization based on its material characteristics, similar to natural sand in construction materials. This research analyzed the characteristics of silica sand from sandblasting waste to develop as construction material. The tests carried out included physical properties (particle size and shape, specific gravity, moisture content, absorption, mud content, specific gravity, and organic content) and chemical properties (X-Ray Fluorescence (XRF) and Scanning Electron Microscope-Energy Dispersive X-Ray tests (SEM-EDX)). The results show that silica sand from sandblasting waste has 548.93 ± 6.46 m average particle size, 2.730 t/m3 specific gravity angular grain with medium sphericity, 0.06% water content, 3.381% absorption capacity, 1.22% mud content, 0.09 kg/liter bulk density, and a clear solution on the organic content test. As chemical content of sandblasting waste, the amount of SiO2, Al2O3, Fe2O3, and CaO are 93.02%, 1.02%, 2%, and 0.63%, respectively. This research concluded that shipyard sandblasting waste has characteristics that can be used as fine aggregate for sustainable building construction materials.